1985
DOI: 10.1111/j.1600-0714.1985.tb00540.x
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical studies of obstructive adenitis in human submandibular salivary glands. I. Immunohistochemical demonstration of lactoferrin, lysozyme and carcinoembryonic antigen

Abstract: Immunohistochemical detection of lactoforrin (LF), lysozyme (LZ) and carcinoembryonie antigen (CEA) was made in obstructive adenitis of the submandibular glands. Atrophic and altered acinar cells in the early stage of the lesion stained strongly for I.F, whereas they were unreactive or stained slightly for LZ. Ductal cells usually stained for LZ Staining for CEA was strong and irregularly distributed in altered acinar cells. Duct‐like structures and dilated ductal segments in the chronic stage were generally n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In obstructive lesions of submandibular glands, EMA distribution is able to serve as a functional marker of both acinar and ductal cells (23). While Gusterson et al (7) failed to detect EMA in the serous acinar cells, and such a staining pattern is quite similar to that of carcinoembryonic antigen (CEA) in serous acinar cells (1,2,26,27). These differences suggest the determinant recognized by monoclonal antibody to human EMA used may have a widely characteristic cross reactivity due to certain glycoprotein or a part of sugar residues.…”
Section: Discussionmentioning
confidence: 99%
“…In obstructive lesions of submandibular glands, EMA distribution is able to serve as a functional marker of both acinar and ductal cells (23). While Gusterson et al (7) failed to detect EMA in the serous acinar cells, and such a staining pattern is quite similar to that of carcinoembryonic antigen (CEA) in serous acinar cells (1,2,26,27). These differences suggest the determinant recognized by monoclonal antibody to human EMA used may have a widely characteristic cross reactivity due to certain glycoprotein or a part of sugar residues.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates the secretory mechanism of LF by acinar cells (185,186). LF is expressed in both normal salivary gland cells and tumors cells (187)(188)(189)(190)(191)(192)(193). In these studies, the coexpression of LF with LY has been demonstrated in salivary gland tumors.…”
Section: Lysozyme Lactoferrin 1 -Antichymotrypsin and 1 -Antitrypsinmentioning
confidence: 86%
“…Pathological findings of obstructive salivary gland lesions have already been described (24). In the initial or early stage atrophied acinar cells and irregularly shaped ductal segments are found as signs of an inflammatory reaction.…”
Section: (C) Obstructive Lesions In the Submandibular Glandmentioning
confidence: 90%